2007
DOI: 10.4049/jimmunol.178.10.6259
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic Targeting of the Human Mannose Receptor Induces Tumor Immunity

Abstract: Pattern recognition receptors are preferentially expressed on APCs allowing selective uptake of pathogens for the initiation of antimicrobial immunity. In particular, C-type lectin receptors, including the mannose receptor (MR), facilitate APC-mediated adsorptive endocytosis of microbial glyconjugates. We have investigated the potential of antigenic targeting to the MR as a means to induce Ag-specific humoral and cellular immunity. hMR transgenic (hMR Tg) mice were generated to allow specific targeting with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
113
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(123 citation statements)
references
References 60 publications
(64 reference statements)
4
113
0
Order By: Relevance
“…Indeed, it has been shown that when DCs fail to mature after taking up the antigen the outcome may be tolerance rather than immunity. 6,8,10,27 In addition, this strategy of targeting the antigen to the same DC which is receiving the TLR stimulation may have advantages over the use of mixtures of antigens and TLR ligands not associated within the same particle or molecule. If a DC encounters the maturation stimuli before seeing the antigen, it will undergo an activation program which will reduce its antigen capture capacity, processing and presentation and will fail to present subsequently encountered antigens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it has been shown that when DCs fail to mature after taking up the antigen the outcome may be tolerance rather than immunity. 6,8,10,27 In addition, this strategy of targeting the antigen to the same DC which is receiving the TLR stimulation may have advantages over the use of mixtures of antigens and TLR ligands not associated within the same particle or molecule. If a DC encounters the maturation stimuli before seeing the antigen, it will undergo an activation program which will reduce its antigen capture capacity, processing and presentation and will fail to present subsequently encountered antigens.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the outcome of the immune response induced by targeting antigens to DCs depends on the receptor used. Targeting DEC205, 8 Lox-1 9 or the mannose receptor 10 induce tolerance if they are not combined with additional adjuvants, while other molecules such as CD40, 11 DC-SIGN, 12 CD91 13 or CD11b/CD18 14 can prime effective antitumor or antiviral responses by themselves. Since maturation of DCs is an essential step to trigger adaptive immune responses, 15 procedures that simultaneously target the antigen to DCs and induce their maturation could lead to the development of a new generation of vaccines that might work in synergy with mild and safe adjuvants.…”
mentioning
confidence: 99%
“…Current data suggest that the ability of CD8␣ ϩ DCs to process exogenous Ags for presentation on MHC class I molecules may be regulated at two levels: 1) differential expression of receptors for endophagocytosis and 2) expression of a specialized pathway to promote the generation of MHC class I peptides (31). Ags captured via the C-type lectin DEC205 and the mannose receptors that are both CD8␣ ϩ specific are cross-presented (5,12). We provide evidence of another CD8␣ ϩ -specific receptor that induces cross-presentation of endocytosed Ags.…”
Section: Discussionmentioning
confidence: 99%
“…Several other molecules like the scavenger receptor Lox-1 (11), the mannose receptor (12), some chemokine receptors (13,14), and TLRs (15,16) have been tested for their potential in immunotherapy. A critical lesson from all of these studies is that some receptors (4,5,11,12), but not others (16,17), require the addition of a DC maturation signal to induce protective immunity. Collectively, it is difficult to predict which strategy among the proposed ones is the most efficient on a comparative basis.…”
Section: Selection Of An Antibody Library Identifies a Pathway Tomentioning
confidence: 99%
See 1 more Smart Citation